Charge states of energetic oxygen and sulfur ions in Jupiter's magnetosphere. Issue 3 (18th March 2016) - Clark, G.; Mauk, B. H.; Paranicas, C.; Kollmann, P.; Smith, H. T.
Abstract: Pitch angle distributions of proton and energetic heavy ion fluxes near Europa's orbit have been measured by the Galileo Energetic Particles Detector (EPD). At similar energies, these distributions have important differences. If their source and transport processes are similar, as we hypothesize here, then it is difficult to reconcile their different pitch angle distributions. By looking at the same question, other researchers have proposed that the heavies are multiply charged, leading to differences in how the particles are lost. This could not be confirmed directly with EPD because that detector does not separate heavy ion measurements by charge state. However, indirect analyses of the data have extracted the charge state of a few sulfur events. We present here a complete list of ion injections observed with EPD over the whole mission. Energetic sulfur and oxygen charge states can be inferred through a dispersion analysis of dynamic injections that makes use of the charge‐dependent nature of the gradient‐curvature azimuthal drift. We find that sulfur is predominantly multiply charged, whereas oxygen is more evenly distributed between singly and doubly charged states. In addition to current theories on energetic heavy ion transport near the Europa region, we propose that charge gain for the oxygen ions (electron stripping) may play an important role in the character of energetic particles in that region. Key Points: Energetic oxygen and sulfur charge states inferred from ion dispersion theory Sulfur is predominantly multiply charged, whereas oxygen is both singly and doubly charged Charge gain plays an important role on energetic oxygen‐neutral interactions in the Europa torus